PERUSAHAAN DAERAH DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN NATUNA TAHUN 2012-2014 - Wan Trisnazilah Sanusi; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study was conducted with the aim to determine what factors affect the decrease in revenue at the Regional Company of Natuna Regency in 2012-2014. The problem in this research is the Regional Company has not been able to contribute optimally to increase PAD. While Natuna Regency has the potential of supporting natural resources to increase PAD. This research uses descriptive analysis method by using qualitative approach. This research is located in Natuna Regency Regional Company. Informants of this study are people who provide information relating to research problems. Data collection techniques used are Observation, interview, and documentation. Regional Company hereinafter referred to as Perusda is a Company which is part or all of the capital owned is owned by the Regional Government, whether derived from separated regional wealth or from APBD, which is managed with the capital wholly or in large part is the result of separated wealth. Regional Company of Natuna Regency is a regional business entity domiciled in Kota Ranai Natuna Regency, established based on Natuna Regency Regulation Number 2 Year 2004. Regional Company is engaged in the business of electricity subsidy, general trading business and services, and others. The Regional Company of Natuna Regency has enough natural resources potential to be developed. The causes of local companies have not been able to contribute in increasing the PAD are: (A) Stagnation Regional Business Field Company, The impact of stagnation of business activities Regional Company is the decline in corporate earnings. (B) The Dilemma of Regional Enterprise Management, Regional Company Management is faced with a difficult problem (dilemma) between applying professionalism with unhealthy organizational conditions. (C) Peruda's supervisory control, the weakness of the supervisory body actually occurs due to the lack of attention of supervisory bodies to the way of perusda. (D) External environmental factors Perusda, including: regional economic stability, regional bureaucracy control, and political intervention. Keywords: Local Government, Regional Company